A sub-supersolution method for nonlinear elliptic singular systems with natural growth and some applications. (February 2016) - Carmona, José; Martínez-Aparicio, Pedro J.; Suárez, Antonio
Abstract: In this paper we give a sub-supersolution method for nonlinear elliptic singular systems with quadratic gradient whose model system is the following − Δ u + v β | ∇ u | 2 u α = f 1 ( x, u, v ) in Ω, − Δ v + u μ | ∇ v | 2 v γ = f 2 ( x, u, v ) in Ω